DEVELOPMENT OF AN END-OF-LIFE CORE MEDICINES LIST FOR COMMUNITY PATIENTS. Issue 2 (1st June 2013) - Tait, P A; Cortis, L; Morris, B
Abstract : Background: Timely access to medicines within the community is important for palliative patients where their preferred place of care is the home environment. This is particularly relevant in the terminal phase of a palliative illness. Commonly encountered symptoms in the terminal phase include: pain, dyspnoea, restlessness, noisy breathing and nausea. While existing national guidelines influence the management of symptoms for palliative patients, the range of medicines usually needed within the community setting to treat noncomplex terminal phase symptoms is less than required in a tertiary inpatient palliative care unit. Aim: To (1) Analyse a variety of palliative resources to identify the pharmacological management of common symptoms in the terminal phase; and (2) Create an end-of-life Core Medicines List that guides consistent prescribing for noncomplex community palliative patients in the terminal phase. Methods: Seven stakeholders representing all consultant-led palliative services in South Australia discussed the management of five common symptoms observed in the terminal phase of a palliative illness. The selection of the core medicines took into consideration cost, availability in the doctor's bag, access to government subsidies (eg, PBS) and drug properties. Results: The five end-of-life core medicines selected for noncomplex community patients are: Clonazepam 1 mg injection; Haloperidol 5 mg/ml injection; Hyoscine butylbromide 20 mg/ml injection; Metoclopramide 10 mg/2 ml injection; and Morphine 10 mg/ml injection Discussion: There is some overlap in the symptoms which these medicines control, thus allowing some options despite the restricted list. Conclusion: A concise end-of-life core medicines list of five medicines has been developed to guide prescribing by community clinicians.